Recurrent fuzzy neural network based system for battery charging - Aliev, R. A.; Aliev, R. R.; Guirimov, B. G.; Uyar, K. (Springer-Verlag Berlin, 2007)
Consumer demand for intelligent battery charges is increasing as portable electronic applications continue to grow. Fast charging of battery packs is a problem which is difficult, and often expensive, to solve using conventional techniques. Conventional techniques only perform a linear approximation of a nonlinear behavior of a battery packs. The battery charging is a nonlinear electrochemical dynamic process and there is no exact mathematical model of battery. Better techniques are needed when a higher degree of accuracy and n-Linimum charging time are desired. In this paper we propose soft computing approach based on fuzzy recurrent neural networks (RFNN) training by genetic algorithms to control batteries charging process. This technique does not require mathematical model of battery packs, which are often difficult, if not impossible, to obtain. Nonlinear and uncertain dynamics of the battery pack is modeled by recurrent fuzzy neural network. On base of this FRNN model, the fuzzy control rules of the control system for battery charging is generated. Computational experiments show that the suggested approach gives least charging time and least T-end-T-start results according to the other intelligent battery charger works.
4th International Symposium on Neural Networks (ISNN 2007) -- JUN 03-07, 2007 -- Nanjing, PEOPLES R CHINA
Keywords: Intelligent